Ni-plated graphite thermal conductive composite absorbing material and its preparation for S-band streaming media harness communication of new energy electric vehicles

By doping Ni graphite-plated raw materials into the wave absorbing matrix and ultrasonic mixing, Ni graphite-plated composite wave absorbing material was prepared, which solved the problem of insufficient thermal conductivity of existing wave absorbing materials, and achieved efficient thermal conductivity and wave absorbing performance. It is suitable for the S-band of streaming media wiring harness communication in new energy electric vehicles.

CN119287351BActive Publication Date: 2025-03-21NANJING XINGYUANYUAN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411816657.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-21
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

While existing wave absorbing materials meet electromagnetic compatibility performance, they lack thermal conductivity, resulting in electronic devices being easily overheated under high power and high integration, affecting equipment performance and safety.

Method used

A Ni graphite-plating thermally-conducting composite wave absorbing material is used to dopate 1%-5% Ni graphite-plating raw materials into the wave absorbing matrix and perform strong dispersion and composite through ultrasonic mixing technology to prepare a material with excellent thermal conductivity and wave absorbing properties.

Benefits of technology

It has achieved a significant improvement in thermal conductivity, with thermal conductivity exceeding the 2 W/m·K of commercial thermal wave absorbing materials in the market, while maintaining good absorption performance and impedance matching performance. It is suitable for the S-band of streaming media wiring harness communication for new energy electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287351B_ABST
    Figure CN119287351B_ABST
Patent Text Reader

Abstract

The invention discloses a Ni-plated graphite heat-conductive composite absorbing material for S-band communication of streaming media harness of new energy electric vehicles and its preparation, and belongs to the technical field of absorbing materials. After obtaining the Ni-plated graphite material by plating a nickel layer on the surface of activated flake graphite by chemical plating, the Ni-plated graphite is used as a heat-conductive filler, and the flaky carbonyl iron is used as an absorbing matrix. The two are ultrasonically dispersed and composited, and then cleaned and dried to obtain the required heat-conductive composite absorbing material. The addition of non-magnetic heat-conductive modified graphite filler not only improves the thermal conductivity, but also improves the impedance matching of the composite absorbing material by adjusting the ratio of the non-magnetic heat-conductive modified graphite filler to the carbonyl iron powder, realizes dielectric regulation, and finally obtains a product with controllable absorbing frequency band and good thermal conductivity. The test results show that the electromagnetic parameters of the product not only meet the electromagnetic absorbing performance requirements of the S-band absorbing material (<-10dB), but also have good thermal conductivity (>3W / m·K), achieving a balance between thermal conductivity and absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of absorbing materials, and specifically relates to a Ni-plated graphite thermally conductive composite absorbing material applied to the S-band of streaming media harness communication of new energy electric vehicles and a preparation method thereof. Background Art

[0002] Electric vehicles, which use drive motors as power output, do not consume fossil energy, and have no tail gas emission problems, have risen rapidly and have developed rapidly with the strong support of the country. With the growth of public demand, people have put forward higher requirements for electric vehicle autonomous driving technology, lithium battery fast charging and endurance technology, including new battery management system technology.

[0003] Streaming media is a technology that provides safety protection for car owners and is widely used in electric vehicles. The frequency band of streaming media technology belongs to the S band (2-4 GHz). It mainly transmits the picture to the display screen in real time without loss and delay through the camera or lidar installed on the vehicle, recording and playing at the same time, achieving an ultra-wide visual field and effectively eliminating blind spots. However, during the operation of electric vehicles, various environmental clutter and inverter AC current signals will cause electromagnetic interference to the signal in the streaming media harness, resulting in the inability to accurately and real-time broadcast the picture, which will hinder the acquisition of information and may threaten the driving safety of the owner.

[0004] To address the above issues, absorbing materials can be used to solve electromagnetic interference problems. Absorbing materials are functional materials that can effectively absorb and attenuate electromagnetic wave energy. They can convert electromagnetic wave energy into other forms of energy dissipation through their internal loss mechanisms, thereby achieving the purpose of absorbing electromagnetic waves.

[0005] However, common absorbing materials generally have the problem of poor thermal conductivity. As the power and integration of modern electronic devices increase, the power density inside the system is getting higher and higher, and a large amount of waste heat is generated during the operation of the equipment. Due to the small internal space and poor air circulation of modern electronic equipment, not only is the electromagnetic wave environment complex, but the waste heat is also difficult to conduct / radiate to the external environment in a timely manner, causing the device temperature to rise, resulting in a decrease in the performance of the equipment or even burning. Therefore, it is very necessary for absorbing materials to meet the electromagnetic compatibility performance while taking into account the thermal conductivity.

[0006] At present, various types of thermally conductive absorbing patches, thermally conductive absorbing coatings, thermally conductive absorbing shells and other products have appeared on the market. These products have the advantages of good electromagnetic clutter absorption function, small size, and easy use. At the same time, the thermal conductivity is better than that of traditional absorbing materials, which can reduce the internal thermal resistance of the equipment, enhance the heat dissipation capacity of the product, and balance the dual problems caused by heat and electromagnetic interference. Chinese patent CN 113717690 A discloses a high thermal conductivity composite absorbing material for radar C band. The document mentions a scheme of forming a thermally conductive absorbing material with pure graphite doped with carbonyl iron. The doping rate of graphite is 20 wt%. Since the conductivity of graphite C is very high, the complex dielectric parameter is very high, so the dielectric matching characteristics are poor. The reflection loss peak of the graphite doped composite thermally conductive absorbing material sample is basically above -3.7dB, and the absorbing performance is obviously insufficient. In addition, in this scheme, the high-content graphite doped sample is only 90% doped (containing 10% paraffin wax), and the low thermal conductivity paraffin wax will also greatly reduce the thermal conductivity of the high-doping concentration graphite. Moreover, excessive doping also shows serious damage to the absorbing performance. Therefore, even if the thermal conductivity of the prepared sample can reach up to 4.3 W / m·K (5+5 sample), it is still not suitable for use as a thermal conductive absorbing material because it does not have good comprehensive thermal conductivity and absorbing properties at the same time. Summary of the invention

[0007] In order to solve the deficiencies in the prior art, the present invention proposes a Ni-plated graphite thermal conductive composite absorbing material for the S-band of streaming media harness communication of new energy electric vehicles. The Ni-plated graphite doping amount is 1%-5% of the mass of the absorbing matrix, and there is no paraffin component. The lower Ni-plated graphite doping concentration can achieve good comprehensive thermal conductivity and absorbing performance, and has excellent impedance matching performance and microwave loss characteristics.

[0008] In order to achieve the above technical objectives, the present invention is implemented by the following technical solutions: a method for preparing a Ni-plated graphite thermal conductive composite absorbing material for S-band streaming media harness communication of new energy electric vehicles, comprising the following steps:

[0009] (1) Degreasing: Add flake graphite powder into sodium hydroxide solution, stir, and wash with water until neutral;

[0010] (2) Coarsening: Add the degreased graphite powder into HNO3 solution, heat in a water bath and stir, then wash with water until neutral;

[0011] (3) Sensitization: Add the roughened graphite powder into SnCl2 solution, stir, and wash with water until neutral;

[0012] (4) Activation: Add the sensitized graphite powder into PdCl2 solution, stir, and wash with water until neutral;

[0013] (5) placing the activated graphite in a chemical plating solution, performing chemical plating in a water bath, washing, and drying to obtain a nickel-plated graphite raw material;

[0014] (6) The nickel-plated graphite raw material and the flaky carbonyl iron powder are ultrasonically mixed in anhydrous ethanol and vacuum dried to obtain the Ni-plated graphite thermal conductive composite absorbing material.

[0015] Furthermore, in step (1), the particle size of the flake graphite powder is 30-40 μm, the concentration of the sodium hydroxide solution is 100-200 g / L, and the stirring time is 30-40 min.

[0016] Furthermore, in step (2), the molar concentration of the HNO3 solution is 10-20 mol%, the water bath temperature is 75-80°C, and the stirring time is 30-40 min.

[0017] Furthermore, in step (3), the concentration of the SnCl2 solution used is 10-20 g / L, and magnetic stirring is performed at room temperature for 10-20 min.

[0018] Furthermore, in step (4), the concentration of the PdCl2 solution used is 0.02-0.03 g / L, and magnetic stirring is performed at room temperature for 10-20 min. After activation, the elemental palladium is distributed on the graphite surface and becomes the activation center of the graphite surface.

[0019] Furthermore, in step (5), the chemical plating solution used contains a main salt NiSO4·6H2O with a concentration of 20-23 g / L, a reducing agent NaH2PO2·H2O with a concentration of 18-20 g / L, a CH3COONa·3H2O with a concentration of 14 g / L, a Na3C5H6O7·2H2O with a concentration of 6 g / L, and deionized water, the pH of the chemical plating solution is 4.0-5.0, the chemical plating process is carried out in a water bath at 75-80°C, the chemical plating time is 40-60 min; the drying temperature is 50-55°C, and the drying time is 2-4 h.

[0020] Furthermore, in step (6), the Ni-plated graphite raw material and the high-performance low-frequency CIP are ultrasonically dispersed and mixed, the ultrasonic power is 120 W, the ultrasonic time is 10-15 min, and the raw material is taken out and dried after ultrasonication, the drying temperature is 50-55°C, and the drying time is 2-4 h.

[0021] The Ni-plated graphite thermal conductive composite absorbing material for the S-band of streaming media harness communication of new energy electric vehicles prepared by the above method uses Ni-plated graphite raw material as thermal conductive filler and low-frequency flaky carbonyl iron powder of absorbing material as absorbing matrix, and the two are strongly dispersed and composited by ultrasonic action.

[0022] Furthermore, the content of the Ni-plated graphite raw material as the thermally conductive filler in the thermally conductive and wave-absorbing composite material is 1-5% of the mass of the wave-absorbing matrix.

[0023] Furthermore, the reflection loss peak value of the thermal conductive composite absorbing material at a thickness of 1-2 mm is within the 2-4 GHz frequency band, that is, within the S band.

[0024] The beneficial effects of the present invention are:

[0025] 1. The thermally conductive and absorbing composite material prepared in the present application uses flaky carbonyl iron (CIP) as an absorbing substrate and a heat-conducting carrier, and nickel-plated graphite material as a heat-conducting filler. The final product can be obtained by ultrasonically mixing a certain ratio of the absorbing substrate and the heat-conducting filler. The thermal conductivity of the obtained composite material is significantly improved, and its thermal conductivity is significantly greater than the thermal conductivity (2 W / m·K) of the existing commercially available thermally conductive and absorbing materials on the market. In addition, the addition of non-magnetic nickel-plated graphite has little effect on the absorbing performance of the composite material, which can achieve a balance between thermal conductivity and absorbing performance;

[0026] 2. This application uses pure composite materials to characterize thermal conductivity (without paraffin filling). A relatively low filling amount (the amount of thermal conductive filler Ni-plated graphite is 1% to 5% of the mass of the absorbent matrix) can effectively improve the thermal conductivity of the composite material. At the same time, low filling can also reduce the adverse effect of the thermal conductive filler on the absorbing performance, thereby better balancing the thermal conductivity and absorbing performance of the composite material.

[0027] 3. The reflection loss peak of the heat-conducting and wave-absorbing composite material Ni-graphite / CIP prepared in this application at a thickness of 1~2 mm is within the 2-4 GHz frequency band, that is, within the S band, which meets the use requirements of the S band of the streaming media harness communication of new energy electric vehicles. Its electromagnetic parameters and thermal conductivity coefficient show that the electromagnetic parameters not only meet the electromagnetic wave absorption performance requirements of the S band wave-absorbing material (<-10dB), but also have good thermal conductivity (>3W / m·K), achieving a balance between thermal conductivity and wave-absorbing performance in special scenarios;

[0028] 4. The addition of non-magnetic thermally conductive modified graphite filler not only serves as a thermally conductive carrier to increase the thermal conductivity of the composite absorbing material, but also can improve the impedance matching of the composite absorbing material by adjusting the ratio of thermally conductive graphite filler to carbonyl iron powder, thereby achieving dielectric regulation, and finally obtaining a thermally conductive composite absorbing material with controllable absorbing frequency band and good thermal conductivity for use in the S-band of streaming media harness communication of new energy electric vehicles;

[0029] 5. Due to the shape anisotropy of flake carbonyl iron, its magnetic permeability can break through the Snoek limit and compensate to a certain extent for the loss of magnetic permeability caused by the introduction of non-magnetic graphite thermal conductive filler; at the same time, the composition ratio of graphite thermal conductive filler and carbonyl iron can be relied on to improve and control the dielectric matching, and the reflection loss peak can be controlled to make it controllable in the S band, while also having good thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a process flow chart for preparing Ni-coated graphite thermal conductive composite absorbing material;

[0031] Figure 2 The XRD patterns of the Ni-coated graphite thermal conductive composite absorbing materials and the Ni-coated graphite raw materials prepared in Examples 1-5;

[0032] Figure 3A This is a scanning electron microscope (SEM) photo of Ni-plated graphite raw material;

[0033] Figure 3B is a scanning electron microscope (SEM) photograph of the Ni-plated graphite thermal conductive composite absorbing material prepared in Example 1;

[0034] Figure 3C is a scanning electron microscope (SEM) photograph of the Ni-plated graphite thermal conductive composite absorbing material prepared in Example 2;

[0035] Figure 3D is a scanning electron microscope (SEM) photograph of the Ni-plated graphite thermal conductive composite absorbing material prepared in Example 3;

[0036] Figure 3E is a scanning electron microscope (SEM) photograph of the Ni-plated graphite thermal conductive composite absorbing material prepared in Example 4;

[0037] Figure 3F is a scanning electron microscope (SEM) photograph of the Ni-plated graphite thermal conductive composite absorbing material prepared in Example 5;

[0038] Figure 4 The figures are statistical graphs of electromagnetic parameter data of the Ni-coated graphite thermal conductive composite absorbing materials and the Ni-coated graphite raw materials prepared in Examples 1-5, wherein (a) is a real part curve of the complex dielectric constant, (b) is an imaginary part curve of the complex dielectric constant, (c) is a real part curve of the complex magnetic permeability, and (d) is an imaginary part curve of the complex magnetic permeability;

[0039] Figure 5 The graphs are the reflection loss variation curves of the Ni-coated graphite thermal conductive composite absorber and pure carbonyl iron prepared in Examples 1-5 as a function of frequency, wherein the coating thickness represented by the small graph (a) is 1.5 mm, and the coating thickness represented by the small graph (b) is 2 mm;

[0040] Figure 6 The small figures (a)-(f) are 3D reflection loss diagrams of the reflection loss of pure carbonyl iron and Ni-coated graphite thermal conductive composite absorber prepared in Examples 1-5 as a function of thickness and frequency;

[0041] Figure 7 It is the thermal conductivity curve of the Ni-plated graphite thermal conductive composite absorbing material and pure carbonyl iron prepared in Examples 1-5. DETAILED DESCRIPTION

[0042] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0043] Example 1

[0044] The preparation method of Ni-plated graphite heat-conductive composite wave-absorbing material for S-band streaming media harness communication of new energy electric vehicles comprises the following steps:

[0045] 1) Preparation of nickel-plated graphite raw materials:

[0046] Activation of graphite: 10 g of flake graphite powder (purchased from Sinopharm Chemical Reagent Co., Ltd.) was taken and placed in a 100 g / L sodium hydroxide solution for degreasing, assisted by magnetic stirring for 30 min, washed with deionized water until neutral and filtered; the degreasing graphite powder was coarsened, that is, the degreasing graphite powder was added to a beaker containing HNO3 solution (molar concentration of 10 mol%), stirred in a water bath at 80°C for 30 min, and washed with deionized water until neutral; the coarsened graphite powder was added to SnCl2 (10 g / L) solution, stirred at room temperature for 10 min for sensitization, and washed with deionized water until neutral; the sensitized graphite powder was added to PdCl2 solution (0.02 g / L) for activation, magnetically stirred at room temperature for 10 min, washed with deionized water until neutral, and elemental palladium was distributed on the graphite surface, becoming the activation center of the graphite surface.

[0047] Preparation of chemical plating solution: main salt NiSO4·6H2O (20 g / L), reducing agent NaH2PO2·H2O (18 g / L), CH3COONa·3H2O (14 g / L), Na3C5H6O7·2H2O (6 g / L) and deionized water, pH=5.0.

[0048] Ni plating treatment: The activated graphite was placed in a chemical plating solution and chemically plated in a water bath at 80°C for 50 min. A uniform nickel layer was plated on the graphite surface. The graphite was then washed alternately with deionized water and anhydrous ethanol for 3 times and vacuum dried at 55°C for 2 h to obtain a nickel-plated graphite raw material.

[0049] 2) Preparation of Ni-plated graphite thermal conductive composite absorbing material:

[0050] 1 g of nickel-plated graphite raw material and 100 g of high-performance low-frequency flaky carbonyl iron powder (the preparation of flaky carbonyl iron is an existing technology and will not be elaborated here) were ultrasonically mixed in anhydrous ethanol at an ultrasonic power of 120 W and an ultrasonic time of 10 min. After the ultrasonic treatment, the mixture was washed and sieved and dried in a vacuum drying oven at 50°C for 4 h to obtain a Ni-plated graphite thermal conductive composite absorber material Ni-graphite / CIP.

[0051] Example 2

[0052] The preparation method of Ni-plated graphite heat-conductive composite wave-absorbing material for S-band streaming media harness communication of new energy electric vehicles comprises the following steps:

[0053] 1) Preparation of nickel-plated graphite raw material: same as Example 1.

[0054] 2) Preparation of Ni-plated graphite thermal conductive composite absorbing material:

[0055] 2 g of nickel-plated graphite raw material and 100 g of high-performance low-frequency flaky carbonyl iron powder were ultrasonically mixed in anhydrous ethanol at an ultrasonic power of 120 W and an ultrasonic time of 10 min. After the ultrasonic treatment, the mixture was washed and sieved, and then dried in a vacuum drying oven at 50°C for 4 h to obtain the Ni-plated graphite thermal conductive composite absorbing material Ni-graphite / CIP.

[0056] Example 3

[0057] 1) Preparation of nickel-plated graphite raw material: same as Example 1.

[0058] 2) Preparation of Ni-plated graphite thermal conductive composite absorbing material:

[0059] 3 g of nickel-plated graphite raw material and 100 g of high-performance low-frequency flaky carbonyl iron powder were ultrasonically mixed in anhydrous ethanol at an ultrasonic power of 120 W and an ultrasonic time of 10 min. After the ultrasonic treatment, the mixture was washed and sieved, and then dried in a vacuum drying oven at 50°C for 4 h to obtain the Ni-plated graphite thermal conductive composite absorbing material Ni-graphite / CIP.

[0060] Example 4

[0061] 1) Preparation of nickel-plated graphite raw material: same as Example 1.

[0062] 2) Preparation of Ni-plated graphite thermal conductive composite absorbing material:

[0063] 4 g of nickel-plated graphite raw material and 100 g of high-performance low-frequency flaky carbonyl iron powder were ultrasonically mixed in anhydrous ethanol at an ultrasonic power of 120 W and an ultrasonic time of 10 min. After the ultrasonic treatment, the mixture was washed and sieved, and then dried in a vacuum drying oven at 50°C for 4 h to obtain the Ni-plated graphite thermal conductive composite absorbing material Ni-graphite / CIP.

[0064] Example 5

[0065] 1) Preparation of nickel-plated graphite raw material: same as Example 1.

[0066] 2) Preparation of Ni-plated graphite thermal conductive composite absorbing material:

[0067] 5 g of nickel-plated graphite raw material and 100 g of high-performance low-frequency flaky carbonyl iron powder were ultrasonically mixed in anhydrous ethanol at an ultrasonic power of 120 W and an ultrasonic time of 10 min. After the ultrasonic treatment, the mixture was washed and sieved, and then dried in a vacuum drying oven at 50°C for 4 h to obtain the Ni-plated graphite thermal conductive composite absorbing material Ni-graphite / CIP.

[0068] Related performance tests

[0069] 1. The physical phase (XRD spectrum) of the Ni-graphite / CIP sample prepared in Example 1-5 is as follows: Figure 2 As shown in the figure, the 1%, 2%, 3%, 4% and 5% marked in the figure respectively represent the doping amount of nickel-plated graphite material in carbonyl iron when preparing samples in Examples 1-5 (that is, the mass fraction of nickel-plated graphite material). It can be seen from the figure that all Ni-graphite / CIP samples have diffraction peaks at 44.5°, 65° and 82.5°, representing the (110), (200) and (211) crystal planes of bcc-Fe, respectively, which indicates that the doping of Ni-plated graphite has no effect on the phase structure of CIP, all of which are α-Fe phases, but all composite samples show the diffraction peak of graphite at 26.58°, which represents the (002) crystal phase of graphite. The diffraction peak positions of Ni-coated graphite raw materials are 26.58°, 44.7°, and 54.7°, representing the (002), (003), and (004) crystal phases of graphite, respectively. The diffraction peak of the Ni (111) crystal plane is also at 44.7°, overlapping with graphite.

[0070] 2. In Examples 1-5, a series of thermally conductive composite absorbers were obtained by doping the flake carbonyl iron with nickel-plated graphite thermally conductive fillers of different mass fractions (respectively 1%, 2%, 3%, 4% and 5%). The SEM (scanning electron microscope) images of the Ni-graphite / CIP samples prepared in Examples 1-5 are shown in Figure 3. It can be seen from the figure that the particle size of the nickel-plated graphite raw material is about 30-40 μm, presenting a thin sheet and long strip. The samples prepared in Examples 1-5 all have a flaky structure, so that the samples have good anisotropy, which is conducive to breaking the Snoek limit.

[0071] 3. Figure 4 The electromagnetic parameters of the Ni-graphite / CIP composite absorbing materials prepared in Examples 1-5 and pure carbonyl iron (referring to the raw material flake carbonyl iron used in Example 1, the same below) are shown, wherein the (a) subfigure shows the real part of the dielectric constant (𝜀′) of each sample. It can be seen from the figure that with the increase of frequency, except for the 𝜀′ value of the samples prepared in Examples 4 and 5, which fluctuates downward, the 𝜀′ values ​​of the other samples all fluctuate upward, and the 𝜀′ values ​​of the samples prepared in Examples 1-5 are all higher than the 𝜀′ value of pure carbonyl iron. It can be seen that the excellent conductivity of graphite will make the 𝜀′ value too high, which is not conducive to impedance matching.

[0072] (b) The small figure shows the imaginary part of the dielectric parameters of each sample, that is, the dielectric loss (𝜀′′). With the increase of frequency, except for the sample prepared in Example 5, the 𝜀′′ values ​​of the samples prepared in the other examples all fluctuate and increase, and except for the Ni-graphite / CIP sample prepared in Example 1, the dielectric loss of the other samples is higher than that of pure carbonyl iron. This shows that doping a certain mass fraction of nickel-plated graphite thermal conductive filler can enhance the dielectric loss capacity. In the 1-18 GHz frequency band, there are many absorption peaks appearing on the 𝜀′′ curve, which may be due to the multi-polarization dispersion caused by interface polarization relaxation and dielectric relaxation. Because the low-frequency dielectric loss depends on the leakage conductance and fluctuates less, the high-frequency dielectric loss is determined by the relaxation polarization loss and the conductivity loss, so the fluctuation amplitude of the curve increases with the increase of frequency.

[0073] (c) The small figure shows the real part of the magnetic permeability (μ') of each sample. The μ' values ​​of the samples prepared in Examples 1-5 and pure carbonyl iron decrease with the increase of frequency, and the difference between them is not big, which is completely consistent with the dispersion characteristics. And the μ' values ​​of the samples prepared in Examples 1-5 after doping with nickel-plated graphite thermal conductive filler are generally lower than the μ' value of pure carbonyl iron. The reason for this phenomenon is that Ni-plated graphite is a non-magnetic material, and its doping will inevitably reduce the magnetic permeability of the composite absorbing material.

[0074] (d) The small figure shows the imaginary part of the magnetic permeability, i.e., the magnetic loss (μ") of each sample. The μ" values ​​of the samples prepared in Examples 1-5 and pure carbonyl iron first increase and then decrease with increasing frequency. The magnetic loss values ​​of the samples prepared in Examples 1-5 are generally lower than that of pure carbonyl iron. All samples reach a maximum value near 4.2 GHz, which may be related to the exchange coupling between the particles and the multiple resonances of the flaky powder.

[0075] 4. Figure 5The relationship between the reflection loss of the Ni-graphite / CIP composite absorber and pure carbonyl iron prepared in Examples 1-5 and the frequency at different thicknesses is shown. It can be seen from the small figure (a) that when the coating thickness is 1.5 mm, the reflection loss peaks of the Ni-graphite / CIP samples and pure carbonyl iron prepared in Examples 1-5 are both located in the S band, which shows that the doping of Ni-coated graphite raw materials does not change the frequency range of the minimum reflection loss peak of high-performance CIP. Among them, the reflection loss peak of the sample prepared in Example 1 is -11.63 dB (located at 3.28 GHz), while the reflection loss peak of pure carbonyl iron is -12.13 dB (located at 3.28 GHz), the peak value is slightly larger but the peak frequency does not change, the peak frequency positions of the samples prepared in other examples are also around 3.28 GHz, but the reflection loss peak is higher, and the reflection loss peak of the sample prepared in Example 5 is -10.035 dB (3.12 GHz).

[0076] It can be seen from the small figure (b) that when the coating thickness is 2 mm, the reflection loss peaks of the Ni-graphite / CIP sample prepared in Example 1 and pure carbonyl iron are almost the same, both are -16 dB and both are at 2.4 GHz. The peak frequencies of the samples prepared in other examples are also around 2.4 GHz, with the highest being the sample prepared in Example 5, whose reflection loss peak is -12.63 dB (located at 2.24 GHz).

[0077] Although the reflection loss gradually increases with the increase of the mass fraction of Ni-plated graphite, since the reflection loss peaks of the samples prepared in the embodiment are all less than -10 dB and the wave absorbing performance is good, the samples still have great practical value.

[0078] 5. In order to understand the reflection loss of Ni-graphite / CIP samples and pure carbonyl iron prepared in Examples 1-5 as a function of thickness (1-2 mm) and frequency (2-18 GHz), a 3D schematic diagram with mapping was prepared, see Figure 6 As can be seen from the figure, the loss peaks of all samples decrease with increasing thickness, and the peak frequencies are all in the range of 2-4 GHz (S band). This reflects that the absorption performance in the S band can be adjusted by changing the thickness and the amount of Ni-doped graphite.

[0079] 6. The thermal conductivity of the Ni-graphite / CIP samples prepared in Examples 1-5 and pure carbonyl iron is compared. The thermal conductivity changes are as follows: Figure 7As shown in the figure, it can be observed that the thermal conductivity of the CIP-doped modified thermal conductive ceramic filler Ni-coated graphite is significantly improved. Based on carbonyl iron, the thermal conductivity of the samples prepared in Examples 1-5 is increased by 13.91%, 21.05%, 33.46%, 43.98% and 57.89%, respectively, and the thermal conductivity gradually increases with the addition of thermal conductive filler. This shows that the thermal conductive ceramic filler Ni-coated graphite can effectively improve the thermal conductivity of the composite material.

[0080] In this scheme, since pure composite materials are used to characterize the thermal conductivity (without paraffin filling), a lower filling amount (1%-5%) can still effectively improve the thermal conductivity of the composite material. At the same time, low filling can also reduce the adverse effect of thermal conductive fillers on the absorbing performance, thereby better balancing the thermal conductivity and absorbing performance of the composite material.

[0081] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A method for preparing Ni-plated graphite thermally conductive composite absorbing material for S-band streaming media harness communication of new energy electric vehicles, characterized in that: The steps include: (1) Degreasing: Add flake graphite powder into sodium hydroxide solution, stir, and wash with water until neutral; (2) Coarsening: Add the degreased graphite powder into HNO3 solution, heat in a water bath and stir, then wash with water until neutral; (3) Sensitization: Add the roughened graphite powder into SnCl2 solution, stir, and wash with water until neutral; (4) Activation: Add the sensitized graphite powder into PdCl2 solution, stir, and wash with water until neutral; (5) placing the activated graphite in a chemical plating solution, performing chemical plating in a water bath, washing, and drying to obtain a nickel-plated graphite raw material; (6) Ultrasonic mixing of nickel-plated graphite raw material and flaky carbonyl iron powder in anhydrous ethanol, and vacuum drying to obtain a Ni-plated graphite thermal conductive composite absorbing material; The content of the thermal conductive filler Ni-plated graphite raw material in the obtained Ni-plated graphite thermal conductive composite absorbing material is 1-5% of the mass of the low-frequency carbonyl iron of the absorbing matrix.

2. The method for preparing the Ni-plated graphite thermally conductive composite absorbing material for the S-band of the streaming media harness communication of the new energy electric vehicle according to claim 1, characterized in that: In step (1), the particle size of the flake graphite powder is 30-40 μm, the concentration of the sodium hydroxide solution is 100-200 g / L, and the stirring time is 30-40 min.

3. The method for preparing the Ni-plated graphite thermally conductive composite absorbing material for the S-band of the streaming media harness communication of the new energy electric vehicle according to claim 1, characterized in that: In step (2), the molar concentration of the HNO3 solution is 10-20 mol%, the water bath temperature is 75-80°C, and the stirring time is 30-40 min.

4. The method for preparing the Ni-plated graphite thermally conductive composite absorbing material for the S-band of the streaming media harness communication of the new energy electric vehicle according to claim 1, characterized in that: In step (3), the concentration of the SnCl2 solution used is 10-20 g / L, and magnetic stirring is performed at room temperature for 10-20 min.

5. The method for preparing the Ni-plated graphite thermally conductive composite absorbing material for the S-band of the streaming media harness communication of the new energy electric vehicle according to claim 1, characterized in that: In step (4), the concentration of the PdCl2 solution used is 0.02-0.03 g / L, and magnetic stirring is performed at room temperature for 10-20 min. After activation, the elemental palladium is distributed on the graphite surface and becomes the activation center of the graphite surface.

6. The method for preparing the Ni-plated graphite heat-conductive composite absorbing material for S-band streaming media harness communication of new energy electric vehicles as claimed in claim 1, characterized in that: In step (5), the chemical plating solution used contains a main salt NiSO4·6H2O with a concentration of 20-23 g / L, a reducing agent NaH2PO2·H2O with a concentration of 18-20 g / L, a CH3COONa·3H2O with a concentration of 14 g / L, a Na3C5H6O7·2H2O with a concentration of 6 g / L, and deionized water. The pH of the chemical plating solution is 4.0-5.

0. The chemical plating process is carried out in a water bath at 75-80°C for 40-60 min; the drying temperature is 50-55°C, and the drying time is 2-4 h.

7. The method for preparing the Ni-plated graphite heat-conductive composite absorbing material for S-band streaming media harness communication of new energy electric vehicles as claimed in claim 1, characterized in that: In step (6), the Ni-plated graphite raw material and the flaky carbonyl iron powder are ultrasonically dispersed and mixed, the ultrasonic power is 120 W, the ultrasonic time is 10-15 min, and the raw material is taken out and dried after ultrasonication, the drying temperature is 50-55°C, and the drying time is 2-4 h.

8. Ni-plated graphite thermal conductive composite absorbing material for S-band streaming media harness communication of new energy electric vehicles, characterized in that: It is prepared according to the preparation method described in any one of claims 1 to 7. The thermally conductive composite absorbing material uses Ni-plated graphite raw material as a thermally conductive filler and low-frequency carbonyl iron absorbing material as an absorbing matrix, and is obtained by strongly dispersing and compounding the two through ultrasonic action.

9. The Ni-plated graphite heat-conductive composite absorbing material for S-band streaming media harness communication of new energy electric vehicles as claimed in claim 8, characterized in that: The content of the Ni-plated graphite raw material as the thermally conductive filler in the thermally conductive composite absorbing material is 1-5% of the mass of the absorbing matrix.

10. The Ni-plated graphite heat-conductive composite absorbing material for S-band streaming media harness communication of new energy electric vehicles as claimed in claim 8, characterized in that: The reflection loss peaks of the thermally conductive composite absorbing material at a thickness of 1-2 mm are all within the 2-4 GHz frequency band, that is, within the S band.

Citation Information

Patent Citations

  • High-thermal-conductivity composite wave-absorbing material applied to radar C wave band and preparation method of high-thermal-conductivity composite wave-absorbing material

    CN113717690A

  • High thermal conductivity wave-absorbing organosilicon composition and preparation method thereof

    CN110294939A

  • Preparation method of Ni / C composite conductive powder

    CN112045182A